Pancreatic cancer risk: Associations with meat-derived carcinogen intake in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial (PLCO) cohort - Anderson, Kristin E.; Mongin, Steven J.; Sinha, Rashmi; Stolzenberg-Solomon, Rachael; Gross, Myron D.; Ziegler, Regina G.; Mabie, Jerome E.; Risch, Adam; Kazin, Sally S.; Church, Timothy R. (Molecular carcinogenesis, 2012)
Background Epidemiological studies report positive associations between high‐temperature cooked meat intake and pancreatic cancer. We assessed associations between dietary intake of heterocyclic amines (HCAs) and benzo(a)pyrene (BaP)—mutagens formed in meat cooked at high temperatures—and incident exocrine pancreatic cancer in a prospective cohort. Methods The 62 581 subjects randomized to screening in the Prostate, Lung, Colorectal, and Ovarian Screening Trial (PLCO) who completed an initial dietary survey that assessed meat intake, cooking methods, and doneness preferences defined the cohort. Subjects were surveyed annually for incident cancers through 2007. A National Cancer Institute research database (CHARRED) was used to estimate HCA and BaP intake and a Mutagenic Activity Index (MAI) from survey data. Proportional hazard ratios (HRs) for risk of pancreatic cancer were estimated from multi‐variate Cox regression models by quintile of intake, with the lowest quintile as the referent. Results During follow‐up (median: 10 yr), 248 cases of exocrine pancreatic cancer were confirmed. Preferences for well and very well done meat were generally associated with increased risks. Significant elevations in pancreatic cancer risk were found in upper quintiles of MAI, and individual mutagens 2‐amino‐3,4,8‐trimethylimidazo[4,5‐f]quinoxaline (DiMeIQx) and 2‐amino‐3,8‐dimethylimidazo[4,5‐f]quinoxaline (MeIQx). Compared to the lowest quintile of MAI, the third and fifth quintiles brought HRs of 1.86 (1.22, 2.85) and 1.87 (1.16, 3.02), respectively. These three exposures exhibited significant (P‐trend: 0.01–0.03) positive trends in risk as their levels increased Conclusion Consuming well‐done meat cooked at high temperatures, which contains high mutagen levels, appears to confer increased risk of pancreatic cancer. © 2011 Wiley Periodicals, Inc.